High intensity interval training negatively affects mood state in professional athletes - Selmi, O.; Ben khalifa, W.; Zouaoui, M.; Azaiez, F.; Bouassida, A. (Science & Sports, 2018)
Objectives: This study aimed to identify the effects of high-intensity interval training (HIIT) on psychological responses and to verify the relationship between Ratings of Perceived Exertion (RPE) and the Profile of Mood State (POMS) scores. Equipment and methods: Twenty male soccer players took part in the study (mean±SD: age=23.85±0.9 years). Training session: 28-min (4×4minutes work interspersed with 3-min of passive recovery). Effort: HIIT: intermittent 10-s runs at 120% maximal aerobic speed interspersed with10-s of passive recovery. Psychological responses were collected before and after HIIT-session using POMS scores (Tension, Anger, Confusion, Depression, Fatigue, and Vigour). RPE was collected after HIIT-session. Results: The HIIT resulted in: an increased anxiety, fatigue, total mood disturbance (TMD) (P<0.05, ES=0.41; P<0.001, ES=0.37; P<0.001, ES=1.48, respectively), a decreased vigor (P<0.001, ES=0.84). No significant correlation was found between POMS scores and RPE (P>0.05). HIIT negatively affected POMS scores. Results support the interest of this tool as one for monitoring mental fatigue and emotional change during training in professional soccer players. Mood state does not seem to be affected by the perceived internal intensity. Additional HIIT to the soccer training sessions promoted different mood states that coaches need to be aware in a way to optimize physical fitness and recovery.